Pengaruh Kompetensi Dan Kepuasan Mengajar terhadap Prestasi Kerja Guru Agama Kristen - Mikha Agus Widiyanto; I Putu Ayub Darmawan (Universitas Kristen Satya Wacana, 2019)
Teaching competence and theoretical satisfaction are factors that influence job performance. Through this research, the author tests, proves and analyzes and makes a causal relationship model the effect of competence and teaching satisfaction on the work performance of Christian Religious Education teachers. The population in this study were Christian Religious Education Teachers in Kutai Kartanegara District, East Kalimantan. The method in this study is Survey - Causal with data analysis techniques using path analysis. The results of data analysis show that: 1) There is positive and significant direct effect between teaching competencies on teaching achievement of Christian Religious Education teachers, 2) There is a positive and significant direct effect of teaching satisfaction on teaching achievement of Christian Religious Education teachers. Increasing teacher competence will have an impact on professionalism in carrying out teaching assignments and have an impact on work performance. Accompanied by high satisfaction makes the teacher responsible for his work and implement it oriented to achievement.